The increasing trend of childhood cancers in Sri Lanka: analysis of National Cancer Registry Data - Sachintha Dilhani; Suraj Perera; Nirma Alpitiarachchi; Mekala Fernando (College of Community Physicians of Sri Lanka, 2022)
Introduction: There is a dearth of information available on baseline data on the pattern of childhood cancers in Sri Lanka.   Objectives: To describe the pattern of childhood cancer in Sri Lanka from 2005 to 2019.   Methods: Data of all newly diagnosed childhood cancer patients (age group 0-19) during 2005-2019 included in the National Cancer Registry, Sri Lanka (NCR-SL) were analysed. Data were categorized according to the frequency of childhood cancers in different age groups, sex, and types of tumours using the International Classification of Childhood Cancer, and incidence rates of childhood cancer were analysed.   Results: During the 15 years studied, 10 276 childhood cancer cases have been reported out of338 866 cancer patients, accounting for 3% of all cancers. Incidence was slightly higher among males, and the male to female ratio was 1.1: 1. Children in the 0-4-year age category accounted for 32% (n=3295) of the burden followed by 15-19 age group (n=3021; 29 .4%). The lowest frequency (n= 1961; 19 .1%) was seen in the 10-14-year age group. The age-standardized incidence rate of childhood cancer was observed to have increased significantly from 2005-2019, with an average annual percent change (AAPC) of 3 .0 (95% CI: 1.1, 4.9). The increase was significant in early life (0-4 and 5-9 age groups). Haematological malignancies accounted for 43.2 % of all childhood cancers. Among children aged 0-14, the first three leading cancers were leukaemia, central nervous system tumours, and lymphomas, whereas, in the 15-19-year age group, other malignant epithelial neoplasms & malignant melanomas were the leading types of cancers, followed by leukaemia and lymphoma.   Conclusions & Recommendations: Childhood cancer incidence rates are increasing in Sri Lanka in parallel with global statistics. A significant increase in childhood cancer cases is observed in early ages of life (0-4 and 5-9 age groups) with a slight male preponderance in all ages.